Vibration of RC beams with NSM CFRP with unbonded/notched circular rod damage. (1st June 2016) - Capozucca, R.; Magagnini, E.
Abstract: The near-surface mounted (NSM) technique using Fiber Reinforced Polymer (FRP) rods inserted into grooves has been shown to be a suitable method in the strengthening of reinforced concrete (RC) beams. Availability of this strengthening is due to bond between concrete–resin-FRP rod and to absence of damage of FRP rods. In this paper, the detection of damages as a consequence of unbonding and/or notches is investigated by dynamic response of RC beams with NSM Carbon-FRP circular rods. The behavior of beams was analyzed through experimental free vibrations on four RC beam models. One of the beams was strengthened with undamaged CFRP rod while three beams presented bond defects between rods and concrete as well as notches in CFRP rods with a reduction of section for a segment. Each beam was subjected to increasing bending loading at different steps and tested dynamically, in the un-cracked concrete state and after every step of loading. Changes of frequency values evaluated by Frequency Response Functions (FRFs) envelope are related to the damage degree of RC beams with NSM CFRP rod. Theoretical results were obtained through numerical modeling of RC beams with CFRP rods: theoretical frequency values are compared with those obtained through tests and discussed.